The long tedious journey of cleft lip and palate patients seeks multidisciplinary approach to smoothen - Hasana, Md Nazmul; Chowdhury, Shirin Sultana (Update Dental College Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/updcj.v4i1.21157 Update Dent. Coll. j: 2014; 4 (1): 01-03